Pelaksanaan KKNT PTMGRMD LLDIKTI IV Untuk Pengembangan Desa Cipicung Kecamatan Cikedal Kabupaten Pandeglang - firasanto, gaguk; Abdillah, Jundi; Amalia, Sari; Risnawati, Eris; Sunardi, Ariyawan (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Thematic Community Service Program (KKN), conducted from September 4 to December 24, 2024, in Cipicung Village, Pandeglang Regency, represents the implementation of the Higher Education Tri Dharma, particularly in community service. This program involved students from various academic backgrounds working collaboratively to design and carry out community-based initiatives aligned with local needs. The primary objective of this activity was to provide students with authentic experiential learning by engaging directly with the community, enabling them to identify issues, formulate solutions, and implement beneficial programs. Over the four-month period, several initiatives were executed, including One Village One Product (OVOP), administrative governance improvement, digitalization of pesantren, MSMEs and village enterprises, anti-drug and online gambling awareness campaigns, innovation development, anti-bullying and motivation counseling, and improvement of village facilities such as signage and office structures. All activities were conducted in collaboration with village authorities, community leaders, and local residents to ensure relevance and sustainability. Overall, the thematic KKN program contributed positively to community empowerment, governance improvement, and local capacity building while simultaneously enhancing students’ academic, social, and professional competencies through experiential learning. Keywords: Thematic KKN, community development, Tri Dharma, students, Cipicung.